2016
DOI: 10.1039/c6cp02983c
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the surface segregation behavior of transition metals on Ni(111): a first-principles study

Abstract: The surface composition of an alloying system has an important impact on its catalytic and chemical properties. The segregation behavior of 3d, 4d and 5d transition metals on an Ni(111) surface has been investigated by performing first-principles calculations in the framework of density-functional theory with the generalized gradient approximation for the exchange-correlation functional. Our calculated surface segregation energies are in good agreement with the experimental data as well as with previous calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 58 publications
(72 reference statements)
1
21
0
Order By: Relevance
“…According to our calculations, ΔEint of Co, Ni, Cu, and Zn is more negative than that of Fe, which implies that these metal atoms are all energetically favorable to form as a single layer on the Fe 3 C surface (Table S2). In our case, the atomic size difference between the substituted metal atom and the Fe atom can influence the segregation . If the substituted metal atoms are in the second layer of the Fe 3 C substrate, the atomic size difference between the substituted metal and Fe increases strain in the bulk structure, and to relieve the strain, the introduced metal atoms in the bulk exchange with Fe atoms at the surface .…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…According to our calculations, ΔEint of Co, Ni, Cu, and Zn is more negative than that of Fe, which implies that these metal atoms are all energetically favorable to form as a single layer on the Fe 3 C surface (Table S2). In our case, the atomic size difference between the substituted metal atom and the Fe atom can influence the segregation . If the substituted metal atoms are in the second layer of the Fe 3 C substrate, the atomic size difference between the substituted metal and Fe increases strain in the bulk structure, and to relieve the strain, the introduced metal atoms in the bulk exchange with Fe atoms at the surface .…”
Section: Resultsmentioning
confidence: 76%
“…Stable heterostructures with Cu and Zn atoms are likelyt o form only with Cu or Zn atomsa tt he interface, unlike Ni and Co substitution. This can be relatedt ot he segregationt hat is relatedc losely to the surface energy [40,41] and atomic radius. [41] According to our calculations, DE int of Co, Ni, Cu, and Zn is more negative than that of Fe, which implies that these metal atoms are all energeticallyf avorable to form as as ingle layer ChemSusChem 2020ChemSusChem , 13,996 -1005 www.chemsuschem.org on the Fe 3 Cs urface (Table S2).…”
Section: Structure Of the Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…26,28,60 Since Rh has a lower HBE value than Ni, 61 the presence of Rh in the alloy may decrease the adsorption energy of hydrogen on the catalyst surface and increase the HOR activity. The calculated values of surface segregation energy 62 indicated that Rh tends to segregate toward the surface of alloyed Ni (111). In addition to the modulation of the HBE by alloying, the intrinsic high activity of Rh ( Figure 3A), partially segregated on the surface, is beneficial for the HOR activity of the NiRh alloy catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…In previous study, Yu et al [46] investigated Mo segregation in MoNi(111) system using DFT, and found Mo atom prefer to stay in second layer. In addition, another work of them considered some transition metals segregation in Ni(111) surface such as W, Mo, V, Fe, Cr [47]. These elements prefer to occupy a site in the second layer.…”
Section: Resultsmentioning
confidence: 99%